Discriminatory pricing of over-the-counter derivatives - Harald Hau; Peter Hoffmann; Sam Langfield; Yannick Timmer (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
New regulatory data reveal extensive discriminatory pricing in the foreign exchange derivatives market, in which dealer-banks and their non-financial clients trade over-the-counter. After controlling for contract characteristics, dealer fixed effects, and market conditions, we find that the client at the 75th percentile of the spread distribution pays an average of 30 pips over the market mid-price, compared to competitive spreads of less than 2.5 pips paid by the bottom 25% of clients. Higher spreads are paid by less sophisticated clients. However, trades on multi-dealer request-for-quote platforms exhibit competitive spreads regardless of client sophistication, thereby eliminating discriminatory pricing.
Keywords: G14; G18; D4; 330; dealer spreads; information rents; RFQ platforms; corporate hedging